Comparative Diagnostic Accuracy of VistaCam IX Proxi and Bitewing Radiography for Detection of Interproximal Caries - Solmaz Valizadeh; Yaser Safi; Azadeh Beigvand; Arash Farahnaki (Shiraz University of Medical Sciences, 2023)
Statement of the Problem: Early detection of caries and the extent of carious lesions for appropriate treatment planning are very important and lead to introduction of new diagnostic tools.Purpose: This study aimed to compare the diagnostic accuracy of VistaCam IX Proxi and bitewing radiography for detection of posterior interproximal caries.Materials and Method: This in vitro study was performed on 40 extracted posterior teeth without cavitated carious lesions. Bitewing radiographs were obtained, infrared (IR) examination was performed, and the teeth were sectioned for histopathological analysis under a stereomicroscope as the gold standard for detection of caries and determination of the extent of carious lesions. Data were analyzed with Cohen's kappa statistic, and Wilcoxon rank sum test.Results: The specificity of VistaCam IX Proxi and bitewing radiography was 71.4% and 87.7%, respectively. Their sensitivity was 100% and 40% for enamel caries, 72.8% and 54.5% for external half dentin caries, and 82.3% and 58.8% for internal half dentin caries, respectively (p= 0.048).Conclusion: Bitewing radiography had a higher specificity and lower rate of false positive results. However, VistaCam IX Proxi had higher sensitivity for caries detection with lower rate of false negative results. Considering the higher sensitivity and significantly lower frequency of false negative results by VistaCam IX Proxi, it may be reliably used for caries detection specially enamel caries, and can serve as an adjunct to bitewing radiography.